EFEK SAMPING OBAT ANTI TUBERKULOSIS (OAT) DAN PENANGANANNYA PADA PASIEN TUBERKULOSIS (TB) DI PUSKESMAS PERUMNAS KOTA KENDARI - Musdalipah Musdalipah; Eny Nurhikma; Karmilah Karmilah; Muh. Fakhrurazi (Jurnal Ilmiah Manuntung, 2018)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis, which mostly (80%) attacks the lungs. Tuberculosis is one of the diseases that attacks people with the relatively high percentage and can effect in death. This study aims to determine how the use of anti-tuberculosis drugs in TB patients cause bad side effects and how the treatment of the side effect.The method of this research is descriptive with cross sectional study design. The sampling techniques are Retrospective and Prospective research. The data tabulation taken by distributed questionnaires and interviews to the TB patients and health worker. The data was collected at the Perumnas public health center of Kendari, which was 21 patients who were undergoing treatment stage and also had fulfilled the inclusion criteria that have been determined. The results showed that 21 tuberculosis patients at the Perumnas public health center of Kendari experienced the side-effects such as nausea and vomiting, hematuria, loss of appetite, fever, joint, itch, and skin redness. The most common side effects were queasy and hematuria with the same percentage of 71,5%. The treatment of side effects done by giving the drugs information and providing the drug therapy in agree with the complaints. Keywords : Tuberculosis, Side-effects, Anti-Tuberculosis